Replika . pismo niezależne Dolny Śląsk, no. 46, 1986 - Norwid, Cyprian, Kamil; Konarski, Feliks; Wałęsa, Lech; Falicki, Paweł (Agencja Wydawnicza Solidarności Walczącej, 1986)
Print run: 1200-2000 copies